Air Pollution and Respiratory Diseases in South Tangerang: A Literature Review - Abdul Rahman; Mukhtar Ikhsan (Respiratory Science, 2026)
In cities, air pollution ranks high among the most pressing problems affecting both the environment and people's health. Research has demonstrated that gaseous pollutants like ozone (O3), sulfur dioxide (SO2), and nitrogen dioxide (NO2), as well as fine particulate matter (PM2.5 and PM10), greatly increase the prevalence of respiratory diseases like asthma, chronic obstructive pulmonary disease (COPD), and acute respiratory infections (ARI). To investigate the effects of air pollution on public health, especially in South Tangerang City, and the correlation between the two, this article provides a thorough literature analysis. The literature search results indicate that air pollution plays a role in the occurrence of ARI, asthma, pneumonia, and COPD through oxidative stress, long-term inflammation, and immune system disorders. Data from local and regional levels show that PM2.5 levels in South Tangerang frequently exceed WHO-recommended limits, particularly during certain periods, increasing the potential for respiratory health problems among urban residents. These emphasize the importance of integrated, evidence-based efforts to control air pollution to protect public health and support sustainable urban development.